Exploration of study skills among professional Accounting students: evidence from Malaysian Public university / Melissa Mam Yudi...[et al.] - Mam Yudi, Melissa; Ahmad, Mahfuz; Sahol Hamid, Nazreen; Yatim, Normahiran; Abdullah, Azizah (Universiti Teknologi MARA, Kedah, 2018)
The purpose of the present study was to explore the dominant study skills of students in preparation for professional accounting examinations and to investigate the existence of any relationship between demographic factors and study skills. A total of 141 male and female first year students pursuing the ACCA professional qualification from Universiti Teknologi MARA (UiTM) participated in the present study by completing a questionnaire on study skills. With regards to the first objective, the findings show students focus more on test strategies, followed by time management, study aids and note taking, organising and processing information and lastly reading and selecting the main idea. As for the second objective, the demographic factors examined in this study are gender, parents' income and whether the student scored "A" for English in high school. The findings of the relationship indicate a significant relationship between parents' income with time management and reading and selecting main ideas, while other demographic factors show no significant relationships. This research contributes an input to the teaching and learning methods which plays an important role in the improvement of students' academic performance.